Problemi z rekordi v športu - Pisk, Jernej (Šport (Ljubljana), 2016)
Part of modern sport is highly influenced with the urge to achieve records. Olympics or World Championships without records would be a big disappointment among spectators and general public alike. But it seems that this moment is inevitably coming. The logic of sport record is based on impossible ideal of unlimited growth in limited systems. The biological human body is finite system which limit the desire for unlimited progress of sport records. What does it mean for record sports? Is this the announcement of its final end or just the incentive for its modification in the direction of more sustainable sport practices?
Keywords: competitiveness; napredek; progress; record; rekordi; sport; sustainable development; šport; tekmovalnost; trajnostni razvoj